Research Progress on the Geological Application of a Flow-Through Time-Resolved Analysis System - Xinning XU; Shuo WANG; Juan XU; Pengfei LIU; Shouye YANG (Yankuang ceshi)
FT-TRA is a rapid reaction (dissolution)-on-line analysis system newly developed in the early 21st century. It consists of an eluent mixing unit, a reaction unit and an analysis unit. Its core function is to wash trace samples in the sample reactor with a specific mobile phase, separate or remove specific components in the sample, and monitor the exsolution characteristics of different elements and mineral components of the sample to achieve high resolution online process analysis. In this article, the technical principle, hardware and software composition, experimental method, operation key points and geological application development process of the FT-TRA system are reviewed. The controversial points in the geological application of the system are explained and analyzed, and its future development direction and potential are forecasted based on its development status. At present, the main geological applications of this system include the verification of proxy indicators for paleoceanography and paleo-environment research (such as foraminifera and ostracod leaching), the study of the mineral dissolution process and reaction kinetics, and the analysis of the elemental phase of environmental samples. The dissolution mechanism of different components involved in the operation of the FT-TRA system is an important problem to be solved in its application process. Further improvement of its dissolution dynamics principle will inevitably provide more new ideas for the future development of the system, such as multi-type geological sample dissolution and mineral simulation synthesis. The BRIEF REPORT is available for this paper at http://www.ykcs.ac.cn/en/article/doi/10.15898/j.ykcs.202304130048.